2014
DOI: 10.7150/ijms.8034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Administration of Forskolin on Glycemia and Oxidative Stress in Rats with and without Experimental Diabetes

Abstract: Forskolin is a diterpene derived from the plant Coleus forskohlii. Forskolin activates adenylate cyclase, which increases intracellular cAMP levels. The antioxidant and antiinflammatory action of forskolin is due to inhibition of macrophage activation with a subsequent reduction in thromboxane B2 and superoxide levels. These characteristics have made forskolin an effective medication for heart disease, hypertension, diabetes, and asthma. Here, we evaluated the effects of chronic forskolin administration on blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…These results suggest that FSK decreases oxidative stress and improves the acute kidney injury of glycerol, this is in agree with [30] that reported the protective effect of chronic administration of forskolin on glycemia and oxidative stress in rats with and without induced diabetes. [31,32] reported that cAMP also increased renal blood flow and glomerular filtration rate suggesting that an intracellular accumulation of cAMP by forskolin may be responsible for the afferent arteriolar dilatation which improves the kidney function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that FSK decreases oxidative stress and improves the acute kidney injury of glycerol, this is in agree with [30] that reported the protective effect of chronic administration of forskolin on glycemia and oxidative stress in rats with and without induced diabetes. [31,32] reported that cAMP also increased renal blood flow and glomerular filtration rate suggesting that an intracellular accumulation of cAMP by forskolin may be responsible for the afferent arteriolar dilatation which improves the kidney function.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies which reported that forskolin decreased the lipid peroxidation in pre-treated erythrocytes and concluded that the antioxidant effect of forskolin could be compared with the effects of probucol and vitamin E [34]. It has been observed that in vitro forskolin increased the level of the antioxidants [19] Also there is anti-inflammatory effect of forskolin which is related to its antagonistic effect on TNFα and also by decreasing the level of inflammatory mediators as histamine, interleukins (IL-1β,IL-4, IL-6, IL-8), leukotriene (LT-4), antigens [30].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of forskolin significantly enhanced the levels of GSH and activity levels of SOD and catalase which precluded LPx and thereby reduced oxidative toxicity in the testis and epididymis of mancozeb‐exposed rats. These results support the earlier findings reporting the use of forskolin in effective treatment against oxidative toxicity …”
Section: Discussionmentioning
confidence: 99%
“…This study is similar with our results. Moreover, FSK has effects of weight loss (Doseyici, Mehmetoglu, Toker, Yerlikaya, & Erbay, 2014), decreasing fasting blood glucose levels (Rios-Silva, Trujillo, Trujillo-Hernandez, et al, 2014), reducing intraocular pressure in patient with glaucoma (Vetrugno et al, 2012), nerve protection (Jensen, Ducray, Widmer, & Meyer, 2015), improving depression (Menninger & Tabakoff, 1997), antitumor (Follin-Arbelet et al, 2015), antiaging (Tumer, Bowman, Larochelle, Kelley, & Scarpace, 1997), and dilating bronchi (Kanne, Burte, Prasanna, & Gujjula, 2015).…”
Section: Effects Of Isof/fsk On Tlr4 Myd88 and Nf-κb In Human Mlsmentioning
confidence: 99%